The development of Malay Dessert Module (Bubur and Pengat) - Abdul Rahman, Abdul Wafi; Md Sahak, Adibah Aishah; Yusri, Nabilah; Raden Ismail, Raden Mohd Farhan Helmy; Rohiat, Mohd Akmal (2021)
Malaysia is one of the few places where one could find an amalgamation of flavors and varieties of heritage food, which stands a living proof of the famous motto Malaysia, Truly Asia. The availability of local resources in this country allows the creation of flavorful, delicious, unique, and authentic recipes. In this modern era, many have forgotten the uniqueness of cooking techniques and practices in Malay cuisine that our ancestors have passed on to us. Although modernization takes place in the foodways, the values associated with other Malay customs that have been practiced by the family and the rest of the Malay community remain until today. There are many types of traditional food in Malaysia, such as dishes and desserts. There are many varieties of desserts that can be found in all states of Malaysia. In the modern days, Malay desserts can be eaten at any time of the day, as a light breakfast, afternoon snack, or dessert. The development of the Malay dessert module “Bubur and Pengat” is an alternative for users to find and learn Malay dessert in Bubur and Pengat” easily. The objectives of the research were to develop a Malay dessert module in “Bubur and Pengat” especially for all who have to take the Culinary Art course and access the utility of a Malay dessert module “Bubur and Pengat” that consists of content, format, clarity and module presentation design. The development of the module used the ADDIE model that consists of five elements to develop the module. The process of making this module is using Microsoft Word and Canva. This module has been developed and produced based on a few key topics. Analyzes of data from experts who validate reviews suggest that these modules work well and have appropriate content based on pastry. As a result of the development of this module, users will be able to easily understand the topics of Malay dessert in “Bubur and Pengat” and the attractiveness of Malay traditional desserts.